Developing a waste minimization awareness model through community based movement: A case study of the I I U M Green Team - Khairusy Syakirin Has-Yun Hashim,; Abdul Hakim Mohamed,; Haneesa Zahidah Mohamed Shah Redza, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
Waste management issues are encountered in almost every nation. Reports and discussion papers retrieved in developed and developing countries alike show that wastes and their management solutions are a common concern and challenge. One of the solutions is implementing the Waste Management Hierarchy. The aim of a Waste Management Hierarchy is to minimize the amount of waste from entering the landfill/dump sites. Three top initiatives in the waste management hierarchy is the 3Rs initiative, i.e. Reduce, Reuse and Recycle. To cultivate a 3R culture in a society, an important start is to educate people with environmental literacy, in particular, university students. This paper aims at exploring the possibility of using a Community Based Movement and Message Learning Approach to develop a Conceptual Waste Minimization Awareness Model (WMAM). The Green Team, a student’s association of the International Islamic University Malaysia (IIUM) was utilized as the case in point.